High strain rate behaviour of nano-quasicrystalline Al93Fe3Cr2Ti2 alloy and composites - Pedrazzini, S; Galano, M; Audebert, F; Siegkas, P; Gerlach, R; Tagarielli, V; Smith, G (Elsevier, 2019)
We demonstrate the outstanding dynamic strength of nano-quasicrystalline Al93Fe3Cr2Ti2 at.% alloy and composites. Unlike most crystalline Al alloys, this alloy exhibits substantial strain rate sensitivity and retains ductility at high strain rates. This opens new pathways for use in safety-critical materials requiring impact resistance.